(untitled) (Scientific journal of the Fergana State University, 2023)
This article shows how Timurid princes, emirs, generals and army chiefs, soldiers depicted in the “Baburname” appear in different images, and the personality, character traits, and psychological aspects of those around them in such comparative images are reproduced in the translations with the meticulousness of Babur.